Aerodynamic performance of a remotely piloted vehicle - Mohd Zulkifly, Abdullah, Assoc. Prof. Dr.; Zurriati, Mohd Ali; Zoeb, Husain (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/